Annual Plan 1970-71 Laccadive, Minicoy and Amindivi Islands - Planning Commission (Planning Commission, 1970)
Language due to the rats is severe as can be seen from the large number of reseated nuts both on the bunches and among strewn about on the J. Period teal rat bunds, bailing with poison, trapping, banding plain sheets etc, are the methods adopted to control them, these could not make any consider reduction in depredation by rats for want proper interest and enthusiasm from the islanders, hunts.
Laccadive, Minicoy and Amindivi Islands